Female entrepreneurial networks and foreign market entry. Issue 1 (20th February 2017) - Rosenbaum, Gitte O.
Abstract : Purpose: The purpose of this paper is to explore the role of networks in the 116 foreign market entries (FMEs) of women-owned small businesses. Design/methodology/approach: A multiple case study based on semi-structured interviews with eight female entrepreneurs in the Danish fashion design industry. Findings: The results show that contrary to the traditional emphasis placed on the role of networks in the internationalization literature, the focal female entrepreneurs only spartanly used networks to expand into new foreign markets. Indeed, networks were used in only 24 of the 116 FMEs. The respondents largely attributed this reluctance to use networks to work-life balance issues and misgivings about knowledge misappropriation. In contrast, the focal entrepreneurs strongly attested to the decisive role played by information and communication technology (ICT) in allowing firms to enter foreign markets without incurring the costs of network membership or compromising their work-life balance. Research limitations/implications: The present study's findings suggest that ICT has a much stronger role in the FME of firms than previously envisioned. Practical implications: The study's findings also have important implications for policymakers and practitioners charged with promoting the international growth of female entrepreneurial ventures. Originality/value: This study is the first of its kind to explore the way in which female entrepreneurs enter new foreign markets.